A Novel Time-Domain Technique for Damage Detection Applied to SHM Using Savitzky-Golay Filter - Anderson De Oliveira, M.; Filho, J. V. [UNESP]; Junior, V. L. [UNESP]; Inman, D. J.; Chang, F. K. (Destech Publications, Inc, 2013)
This paper presents a novel damage detection approach for Structural Health Monitoring (SHM) systems, which is based on Savitzky-Golay filter and time-domain analysis. In this technique, a specific PZT (actuator) excites the structure and three other ones are used as sensors to receive the structural responses. This method is quite similar to Lamb wave based methods, but the excitation procedure and the analysis of the response signals are different. For the proposed method, a wide band chirp signal, with low amplitude and variable frequency, is used to excite the structure. The response signals are acquired in time-domain and smoothed by a Savitzky-Golay filter, and from the filtered signals the first and second derivatives are computed. CCDM (Correlation Coefficient Deviation Metric) indices are calculated from all signals (smoothed, first and second derivatives), considering the structure a healthy condition as a reference (baseline). Practical tests were carried out on an aluminum plate and the results have demonstrated the effectiveness of the proposed method.